Identification of Genetic Variants Associated with Chronic Kidney Disease Using Restriction Fragment Length Polymorphism : Genetic Variants Associated with CKD Using Restriction Fragment Length Polymorphism - Qureshi, Zahid Habib; Iftikhar, Mehwish; Ihsan, Amna; Farooq, Bakhtawar; Javaid, Asghar; Asghar, Shoaib; Khan, Muhammad Jamal (Pakistan Journal of Health Sciences, 2026)
Chronic kidney disease (CKD) is one of the most common kidney diseases that poses serious health risks. Objective: To identify the genetic variants associated with CKD. Methods: A cross-sectional study was conducted among 183 participants at Ibn-e-Sina Hospital, Multan, from Nov 2023 to May 2024. Klotho (KL), Catalase (CAT), Cyclophilin (Cyp), tumor protein p53 (p53), and Superoxide dismutase 1 (SOD1) were selected for polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Primers were designed via Primer3Plus and confirmed through SnapGene. In-silico RFLP involved NEBcutter and SnapGene for the construction of the sequence map and the mutated band. Wet lab RFLP involved DNA cleavage by restriction enzymes. After PCR incubation, samples were visualized via gel electrophoresis. The T-Coffee tool aligns sequences, enabling the identification of variations in amino acids. Results: The target genes were successfully amplified in the CKD patients before proceeding to RFLP analysis. TaqI, EcoRI, AlwI, and AccI restriction enzymes were selected from in-silico Sequence Maps to cut the band of SOD1, Cyp, KL, and p53 genes, respectively. Cleaved bands of mutated sequences were obtained. The alignment of wild-type to mutated with T-Coffee tool revealed six amino acid substitutions in CAT (Asp/Asn, Asp/Gly, Tyr/Asp, Lys/Arg, Gln/Ser and Ala/Val) and single amino acid substitutions in KL (Phe/Val), Cyp (Ser/Thr), SOD1 (Gly/Arg) and p53 (Leu/unknown). Conclusions: The current study identified genetic variants in KL, CAT, Cyp, p53, and SOD1 genes that may influence CKD progression and therapy.